Geographical Distribution of Indigenous Saccharomyces cerevisiae Strains Isolated from Vineyards in the Coastal Regions of the Western Cape in South Africa - van der Westhuizen, T.J.; Augustyn, O.P.H.; Pretorius, I.S. (South African Journal of Enology and Viticulture, 2017)
Notwithstanding numerous studies on the yeast biota of grapes and grape must, the origin of the primary wine yeast Saccharomyces cerevisiae has been rather controversial. One school of thought claims that the primary source of S. cerevisiae is the vineyard, whereas another believes that ecological evidence points to a strict association with artificial, man-made environments such as wineries and fermentation plants. One of the main thrusts of these kinds of investigations is to understand the succession of yeasts during fermentation of wine and to determine the actual contribution of indigenous strains of S. cerevisiae and wild yeast species to the overall sensorial quality of the end product, even in guided fermentations using selected S. cerevisiae starter cultures. There is increasing interest within the wine community in the use of indigenous strains of S. cerevisiae and mixed starter cultures, tailored to reflect the characteristics of a given region. Against this background we have launched a comprehensive and long overdue biogeographical survey systematically cataloging yeasts in different climatic zones of the 350-year-old wine-producing regions of the Western Cape. The present paper represents the first phase of this programme aimed at preserving and exploiting the hidden oenological potential of the untapped yeast biodiversity in South Africa’s primary grape-growing areas. Grapes were aseptically harvested from 13 sites in five areas in the coastal regions of the Western Cape. After fermentation, 30 yeast colonies per sample were isolated and examined for the presence of S. cerevisiae. Five sampling sites yielded no S. cerevisiae. CHEF-DNA analysis revealed the presence of 46 unique karyotypes in eight of the remaining sites. No dominant strain was identified and each site had its own unique collection of strains. The number of strains per site varied from two to 15. Only in four cases did one strain appear at two sites, while only one instance of a strain occurring at three sites was recorded. All sites contained killer and sensitive strains; however, killer strains did not always dominate. Commercial strains were recovered from three sites. Although commercial yeasts dominated the microflora at two sites, it appears that fears of commercial yeasts ultimately dominating the natural microflora seem to be exaggerated.